(-2-n)+(6n-7)=

Simple and best practice solution for (-2-n)+(6n-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2-n)+(6n-7)= equation:


Simplifying
(-2 + -1n) + (6n + -7) = 0

Remove parenthesis around (-2 + -1n)
-2 + -1n + (6n + -7) = 0

Reorder the terms:
-2 + -1n + (-7 + 6n) = 0

Remove parenthesis around (-7 + 6n)
-2 + -1n + -7 + 6n = 0

Reorder the terms:
-2 + -7 + -1n + 6n = 0

Combine like terms: -2 + -7 = -9
-9 + -1n + 6n = 0

Combine like terms: -1n + 6n = 5n
-9 + 5n = 0

Solving
-9 + 5n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 5n = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 5n = 0 + 9
5n = 0 + 9

Combine like terms: 0 + 9 = 9
5n = 9

Divide each side by '5'.
n = 1.8

Simplifying
n = 1.8

See similar equations:

| 5+2(9x-4)=4x+7 | | 2(6-5x)+6=8-5x | | 9/5=x/20 | | y=-4x+28x-171 | | 40/64=10/t | | 25/12x=30 | | -11-3(2*-11-7)= | | 2(2x-9)-5=2(x-5)-3 | | 25-12x=30 | | 7x-(2x+17)=18 | | 49=7/8(v) | | -7=-5a-2a | | 2x+11=-9x-18 | | 9(z-6)=4(z-4) | | 9(x+5)=9(x+10) | | t=3+14t-5t^2 | | h(t)=3+14t-5t^2 | | -2x+2=-1 | | 5s+2=5c-2 | | -5n+3=-22 | | 2x+13=-3x-20 | | -1/5x=-12 | | 5t-4=-14 | | (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 |

Equations solver categories